UJI FITOKIMIA DAN AKTIVITAS ASAM SUNTI (Averrhoa bilimbi L.) SEBAGAI ANTIMIKROBA - Misrahanum Misrahanum; Nia Ayuningrum; Hira Helwati (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
Many plants that have potential as antimicrobial agents are found in Indonesia. One of them is bilimbi (Averrhoa bilimbi L.) which comes from the Oxalidaceae family. People in Aceh usually process the fruit into asam sunti. This research was conducted to determine the phytochemical, characterization simplicia, extract, and antimicrobial activity of the asam sunti methanol extract. Phytochemical tests were done using two methods that are the addition of reagents and thin-layer chromatography (TLC). Phytochemical results in each test showed that the asam sunti methanol extract contained alkaloids, flavonoids, tannins, saponins, steroids, and triterpenoids. The water content, water-soluble extract content, ethanol-soluble extract content and total ash obtained was 4,6; 46,6; 54,16 and 39,6% for simplicia and extract respectively, with a value of 22; 42.6; 47.6, and 10.3%. Antimicrobial activity testing used a diffusion well at various concentrations 10; 20; 30; 40 and 50%. The smallest inhibition zone results were obtained at a concentration of 10% with a range of the inhibition zone is 7.43-7.86mm. The biggest antimicrobial activity was found at a concentration of 50% with an inhibition zone of 17.76; 10.63 and 8.7 mm for bacteria and fungi, respectively. in conclusion, the results showed that asam sunti methanol extract was more active in inhibiting the growth of Staphylococcus aureus bacteria than Escherichia coli bacteria and Candida albicans fungi.